Common and unique associations of adolescents' affective and cognitive empathy development with conflict behavior towards parents. (February 2016) - Van Lissa, Caspar J.; Hawk, Skyler T.; Branje, Susan; Koot, Hans M.; Meeus, Wim H.J.
Abstract: Adolescents' development of two empathy dimensions, affective empathic concern and cognitive perspective taking, may be associated with shifts towards more constructive behaviors in conflict with parents. This six-year longitudinal study (ages 13–18) used multivariate latent growth curve modeling to investigate correlations between the developmental trajectories of adolescents' ( N = 497) empathic dispositions and trajectories of their conflict behaviors towards both parents. There were some similarities between the associations of both empathy dimensions with conflict behaviors. Both empathy dimensions were associated with reduced conflict escalation with mothers, and increased problem solving with both parents. However, these associations were consistently stronger for perspective taking than for empathic concern. Furthermore, higher levels of compliance with mothers in early adolescence were uniquely associated with over-time increasing empathic concern. Perspective taking was uniquely associated with decreased withdrawal from conflicts. Perspective taking thus appears to be more strongly associated with a pattern of constructive conflict behaviors.